Application of the mantle cloak in near vertical incidence skywave/ground wave high frequency communication. Issue 14 (14th August 2019) - Ghasemi Mizuji, Ensiyeh; Abbasi Arand, Bijan; Forooraghi, Keyvan; Abdolali, Ali; Derafshi, Iman
Abstract : In this study, the authors propose a new idea to employ mantle cloaking in order to reduce the mutual coupling between electrically small antennas (ESAs) placed on man‐pack radio systems. They determined and numerically optimised the parameters of the mantle cloak on loop and monopole antennas; these antennas are to provide near vertical incidence skywave (NVIS) and ground wave high frequency (HF) communication in man‐pack radio systems. The authors' designed cloak can effectively minimise the mutual coupling between the ESAs – in the man‐pack radios – for only a very small impact on the antenna's radiation characteristics. The authors believe that these improvements pave the way toward effectively applying these compact radio structures in emergency HF communication in areas with limited access to conventional communication links.